2021
DOI: 10.26633/rpsp.2021.39
|View full text |Cite
|
Sign up to set email alerts
|

Childhood hunger experiences and chronic health conditions later in life among Brazilian older adults

Abstract: Objectives. To assess the association between childhood hunger experiences and the prevalence of chronic diseases later in life. Methods. A cross-sectional study was conducted using baseline data from the Brazilian Longitudinal Study of Aging (ELSI-Brazil), a nationally representative study of persons aged 50 years and older (n = 9 412). Univariate and bivariate analyses were used to describe the sample, and multivariate logistic regressions to examine the association between childhood hunger and hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Inadequate food intakes and disease conditions have been revealed in studies (Duong et al, 2018;Khan et al, 2018). A cross-sectional survey conducted using baseline data from Brazilian longitudinal study showed association between childhood hunger and chronic diseases like: diabetes and osteoporosis in later life (adulthood) (Felix-Beltran and Seixas, 2021). This implies that inadequate dietary food intakes and diseases outcome are intrinsically related (Figure 3).…”
Section: Heavy Metals and Malnutritionmentioning
confidence: 99%
“…Inadequate food intakes and disease conditions have been revealed in studies (Duong et al, 2018;Khan et al, 2018). A cross-sectional survey conducted using baseline data from Brazilian longitudinal study showed association between childhood hunger and chronic diseases like: diabetes and osteoporosis in later life (adulthood) (Felix-Beltran and Seixas, 2021). This implies that inadequate dietary food intakes and diseases outcome are intrinsically related (Figure 3).…”
Section: Heavy Metals and Malnutritionmentioning
confidence: 99%
“…For example, adolescents who experience food insecurity are at higher risk of mental health and psychosocial problems (e.g., social behavioral problems and worse academic performance) [ 1 , 6 , 7 ], overweight and obesity [ 8 , 9 ], and risky health behaviors (e.g., risky sexual activity [as a means to acquire food] and substance use) [ 10 , 11 ]. Moreover, hunger in youth increases the risk of chronic disease in adulthood, including, for example, diabetes and osteoporosis [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%